A multicenter, prospective, single arm, open label, observational study of sTMS for migraine prevention (ESPOUSE Study) - Starling, Amaal J; Tepper, Stewart J; Marmura, Michael J; Shamim, Ejaz A; Robbins, Matthew S; Hindiyeh, Nada; Charles, Andrew C; Goadsby, Peter J; Lipton, Richard B; Silberstein, Stephen D; Gelfand, Amy A; Chiacchierini, Richard P; et al. (Cephalalgia, 2018)
Objective To evaluate the efficacy and tolerability of single pulse transcranial magnetic stimulation (sTMS) for the preventive treatment of migraine. Background sTMS was originally developed for the acute treatment of migraine with aura. Open label experience has suggested a preventive benefit. The objective of this trial was to evaluate the efficacy and tolerability of sTMS for migraine prevention. Methods The e Neura S pringTMS P ost-Market O bservational U .S. S tudy of Migrain e (ESPOUSE) Study was a multicenter, prospective, open label, observational study. From December 2014 to March 2016, patients with migraine (n = 263) were consented to complete a 1-month baseline headache diary followed by 3 months of treatment. The treatment protocol consisted of preventive (four pulses twice daily) and acute (three pulses repeated up to three times for each attack) treatment. Patients reported daily headache status, medication use, and device use with a monthly headache diary. The primary endpoint, mean reduction of headache days compared to baseline, was measured over the 28-day period during weeks 9 to 12. The primary endpoint was compared to a statistically-derived placebo estimate (performance goal). Secondary endpoints included: 50% responder rate, acute headache medication consumption, HIT-6, and mean reduction in total headache days from baseline of any intensity. Results Of a total of 263 consented subjects, 229 completed a baseline diary, and 220 were found to be eligible based on the number of headache days. The device was assigned to 217 subjects (Safety Data Set) and 132 were included in the intention to treat Full Analysis Set. For the primary endpoint, there was a −2.75 ± 0.40 mean reduction of headache days from baseline (9.06 days) compared to the performance goal (−0.63 days) (p < 0.0001). The 50% responder rate of 46% (95% CI 37%, 56%) was also significantly higher (p < 0.0001) than the performance goal (20%). There was a reduction of −2.93 (5.24) days of acute medication use, headache impact measured by HIT-6, −3.1 (6.4) (p < 0.0001), and total headache days of any intensity −3.16 days (5.21) compared to the performance goal (−0.63 days) (p < 0.0001). The most common adverse events were lightheadedness (3.7%), tingling (3.2%), and tinnitus (3.2%). There were no serious adverse events. Conclusions This open label study suggests that sTMS may be an effective, well-tolerated treatment option for migraine prevention. Trial registration number NCT02357381